Fracture-healing effects of Rhizoma Musae ethanolic extract: An integrated study using UHPLC-Q-Exactive-MS/MS, network pharmacology, and molecular docking - Jian Zhang; Wanyan Shen; Fanzhi Liu; Hehe He; Shuquan Han; Lina Luo (PLoS ONE, 2025)
Background Fracture disrupts the integrity and continuity of the bone, leading to symptoms such as pain, tenderness, swelling, and bruising. Rhizoma Musae is a medicinal material frequently utilized in the Miao ethnic region of Guizhou Province, China. However, its specific mechanism of action in treating fractures remains unknown. This study aimed to elucidate the chemical constituents of the ethanol extract of Rhizoma Musae (EERM) and investigate its fracture-healing mechanism using network pharmacology. Methods The chemical profile of EERM was characterized via UHPLC-Q-Exactive-MS/MS. Subsequently, a comprehensive network of compounds, targets, and pathways was constructed using network pharmacology approaches. The interactions between the active compounds of EERM and their targets were validated through molecular docking, molecular dynamics simulation and in vitro cell experiments. Results EERM contained 522 identified compounds. Topological analysis of the protein-protein interaction (PPI) network identified 59 core targets, including key proteins like AKT1, IL-6, and EGFR, known for their anti-inflammatory properties and ability to enhance bone cell proliferation and differentiation. Gene Ontology analysis indicated the involvement of EERM in biological processes such as peptidyl-serine phosphorylation, response to xenobiotic stimulus, and nutrient level regulation. KEGG analysis suggested that EERM’s mechanism may involve signaling pathways such as PI3K-Akt, lipid and atherosclerosis, EGFR tyrosine kinase inhibitor resistance, and MAPK pathways. Molecular docking and molecular dynamics simulations results demonstrated a strong binding affinity between the main compounds of EERM and key targets. In vitro cell experiments demonstrate that EERM enhances cell proliferation by upregulating the expression levels of EGFR and STAT3, while simultaneously downregulating AKT1 and CASP3. Conclusion This study investigates the potential active compounds of EERM and its key targets in regulating multiple pathways of fracture, leading to promoting bone cell proliferation. These results offer valuable insights for the future development and clinical application of Rhizoma Musae.